Contemporary Ijtihad Methodology in Pesantren Traditions: Typologies and Constructions - Rohmah, Siti; Ade Nathali Juwita Ningrum; Faiqatul Jannah; Salamah, Ummi; Shalihah, Aidatus (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2025)
Contemporary Ijtihad Methodology in Pesantren Traditions: Typologies and Constructions examines how modern fiqh scholars respond to emerging legal questions through methodological renewal within pesantren-based intellectual traditions. The study addresses the gap between classical juridical frameworks and contemporary social realities, particularly in relation to the role of pesantren as custodians of Islamic scholarly authority. Using a qualitative library research design and descriptive-critical analysis, this article investigates the typologies of contemporary ijtihad and the epistemological foundations that shape them. The findings show that contemporary ijtihad develops through several patterns, including selective, creative, combined, and maslahah-oriented approaches, each reflecting different ways of balancing textual fidelity and contextual relevance. Yusuf al-Qaradawi’s thought is especially significant because it integrates Qur’anic and Hadith-based reasoning, maqasid al-shari‘ah, and collective ijtihad as key methodological principles. The study also indicates that pesantren traditions provide an important ethical and intellectual environment for sustaining adaptive legal reasoning without abandoning normative continuity. In conclusion, contemporary ijtihad is not a rupture from classical scholarship, but a constructive extension that enables Islamic law to remain responsive, credible, and socially meaningful in changing times.